Mahmud Yunus: Pelopor Pola Baru Penulisan Tafsir al-Qur’ān Indonesia - Jauhar Azizy; Muhammad Anwar Syarifuddin (ILMU USHULUDDIN, 2015)
A new pattern of writing Indonesian tafsir emerges from the modernists desire to publish Qur’ānic commentary in Indonesian language. Mahmud Yunus was the first Muslim scholar who wrote theTafsir Qur’an Karim as the first Indonesian Qur’ānic commentary in the modern era. Three elements of modernity marking the new pattern of modern Indonesian Qur’ānic commentary were introduced by Mahmud Yunus, namely the use of Latin alphabets, the brief character of writing, and the introduction of scientific tendency, all of which can be considered the newly invented elements of modern Qur’ānic commentary. Being analyzed from a socio-hermeneutical perspective this piece investigates the ingredients of Mahmud Yunus’ reforming ideas interpolated along the course of his academic and cultural backgrounds.In addition, this writing also extrapolates the wider angle of sosial dynamics within Indonesian academic climate from the second half of the twentieth century.